The Role of Green Marketing and Brand Image in Building Consumer Loyalty in Environmentally Friendly Culinary MSMEs in Malang City: Sustainable Marketing Strategy for Business Continuity - sanita; shohib muslim; Farida Akbarina; Evi Suwarni; nurul hidayatinnisa (Universitas muhammadiyah malang, 2025)
This study aims to analyze the role of green marketing and brand image in building consumer loyalty in environmentally friendly culinary Micro, Small, and Medium Enterprises (MSMEs) in Malang City. The emergence of sustainable consumerism has driven MSMEs to adopt eco-friendly practices such as the use of organic raw materials, biodegradable packaging, and sustainable production processes. Green marketing and a strong brand image are considered strategic levers to enhance consumer trust and loyalty. A quantitative explanatory approach was employed with a sample of 123 respondents, exceeding the targeted 100, selected through purposive sampling of consumers familiar with eco-friendly culinary products. Data were collected through structured questionnaires and analyzed using multiple regression in SPSS. Results indicate that both green marketing and brand image have significant positive effects on consumer loyalty, both partially and simultaneously. The coefficient of determination (R² = 0.751) demonstrates that 75.1% of consumer loyalty can be explained by green marketing and brand image, with brand image showing a stronger influence (β = 0.624) compared to green marketing (β = 0.289). The findings emphasize the importance of authentic sustainability practices and strong brand positioning for MSMEs to compete effectively in the growing eco-conscious market. Theoretically, the research contributes to sustainable marketing literature by confirming the relevance of green value and image in loyalty formation. Practically, it provides recommendations for MSMEs to enhance competitive advantage through green innovation and consistent branding.